U-TH ZONATION-DEPENDENT ALPHA-EJECTION IN (U-TH)/HE CHRONOMETRY - Hourigan J.K.; Reiners P.W.; Brandon M.T. (My University, 2005)
Both theoretical and empirical evidence shows that intracrystalline U-Th heterogeneity in zircon can lead to biases in (U-Th)/He ages if not accurately accounted for in a-ejection corrections. We present a model for age correction for U-Th zoned crystals. We apply this to spherical and prismatic grains with bipyramidal terminations. The spherical calculation is simplistic but allows rapid calculation of the approximate effects of a wide variety of U-Th zoning patterns. The bipyramidal calculation is computationally intensive but permits an more complete estimate of the combined effects of crystal morphology and source zoning as relevant to zircon. Our principle findings are: (1) the assumption of U-Th homogeneity can result in errors of up to similar to 30% (in rare cases, higher) for ejection-corrected ages for typical grain sizes and realistic zonation. (2) Tetragonal prisms with bipyramidal terminations, which are typical of most zircons, exhibit bulk retentivities that can differ by several percent from models considering crystals with pinacoidal terminations. When extreme cases, such as dipyramids, are considered, the bias can exceed 10% or more. (3) Morphologic effects can be accounted for to better than 1 % precision by using new second-order polynomial parameters that describe retentivity as a function of surface-area-to-volume ratio calculated through more complete analysis of crystal dimensions including the height of pyramidal crystal sections. We illustrate application of our model using U-Th concentration profiles determined from single zircons by laser ablation ICP-MS from zoned Tardree Rhyolite zircons.